Water and society: new problems faced, new skills needed - Molle, Francois (Wiley, 2002)
In the last two decades water has clearly moved from the purview of experts and engineers to a wider forum where stakeholders articulate different claims, values and interests around water management issues. This article takes the example of current debates on water resource development in the Mekong basin and re ects on what are the current challenges, the visions of the future that are in con ict and the skills available. It re ects on the extent to which new practices have been incorporated in water-related decision-making and reviews the implications in terms of skills needed for tomorrow's water management.